Allergenic protein-induced type I hypersensitivity models: a review - Feng, Yanhua; Xu, Liangyu; Zhang, Jinming; Bin, Jinlian; Pang, Xialing; He, Sheng; Fang, Lei (Frontiers in Allergy, 2024)
ContextType I hypersensitivity affects approximately one-third of the global population. As the pathophysiology underlying the development of type I hypersensitivity (asthma, food allergy, and anaphylactic shock, etc.) is complex and heterogeneous, animal model studies continue to be the key to identifying novel molecular pathways and providing therapeutic strategies.ObjectiveSelection of the animal model should be done with careful consideration of the protocol variables, animal species, and strains to accurately reflect the clinical symptoms typical of humans.MethodsThe following databases were searched: PubMed and Web of Science.Results and conclusionForeign allergens include allergenic proteins and chemical haptens. This review summarizes the various methods used for designing animal models of common allergenic protein-induced type I hypersensitivity, namely, passive anaphylaxis model, active systemic anaphylaxis/anaphylaxis shock model, food allergy model, asthma model, and IgE-mediated cell models. Additionally, we summarize shrimp tropomyosin-induced type I hypersensitivity models from our previous studies and discuss their advantages and limitations compared with that of ovalbumin-induced models.